Evidence needed to manage freshwater ecosystems in a changing climate: turning adaptation principles into practice - Wilby, R; Orr, H; Watts, G; Battarbee, R; Berry, P; Chadd, R; Dugdale, S; Dunbar, M; Elliot, J; Extence, C; Hannah, D; Holmes, N; et al. (Elsevier, 2010)
It is widely accepted that climate change poses severe threats to freshwater ecosystems. Here we examine the scientific basis for adaptively managing vulnerable habitats and species. Our views are shaped by a literature survey of adaptation in practice, and by expert opinion. We assert that adaptation planning is constrained by uncertainty about evolving climatic and non-climatic pressures, by difficulties in predicting species- and ecosystem-level responses to these forces, and by the plasticity of management goals. This implies that adaptation measures will have greatest acceptance when they deliver multiple benefits, including, but not limited to, the amelioration of climate impacts. We suggest that many principles for biodiversity management under climate change are intuitively correct but hard to apply in practice. This view is tested using two commonly assumed doctrines: “increase shading of vulnerable reaches through tree planting” (to reduce water temperatures); and “set hands off flows” (to halt potentially harmful abstractions during low flow episodes). We show that the value of riparian trees for shading, water cooling and other functions is partially understood, but extension of this knowledge to water temperature management is so far lacking. Likewise, there is a long history of environmental flow assessment for allocating water to competing uses, but more research is needed into the effectiveness of ecological objectives based on target flows. We therefore advocate more multi-disciplinary field and model experimentation to test the cost-effectiveness and efficacy of adaptation measures applied at different scales. In particular, there is a need for a major collaborative programme to: examine natural adaptation to climatic variation in freshwater species; identify where existing environmental practice may be insufficient; review the fitness of monitoring networks to detect change; translate existing knowledge into guidance; and implement best practice within existing regulatory frameworks.